اقتناء الأنظمة الآلیة فى المکتبات المدرسیة: دراسة تطبیقیة على المکتبات المدرسیة بمحافظة قنا - محمود أبو الفضل ضوى (المجلة الدولية لعلوم المكتبات والمعلومات)
This study aims to shed light on the automated systems used in schoollibraries through identify ways and means and procedures for their acquisitionbased on the policies and needs of the school library, and in line with its servicesand activities provided to facilitate the selection of the best system to meet these,The study also aimed to identify the person who chooses these systems, theirrole, responsibilities and motives behind the desire to use and acquire automatedsystems in school libraries instead of the traditional methods of work and toidentify the obstacles that prevent the acquisition of school libraries in QenaGovernorate by automated systems or optimal use of them.The study relied on the field approach for collecting and analyzing datarelated to the research topic through the questionnaire form.The study reached many results, the most important of which are that thelibrary specialist is the first responsible for the decision to choose automatedsystems in school libraries in Qena Governorate and there is no unified andpractical policy followed when choosing automated systems in school libraries inQena Governorate, the extent of the severe need for these libraries. To acquireautomated systems and rely on them to provide the required services anddispense with traditional work in the performance of office tasks, as well as thedesire to provide new services to the beneficiaries through automated systems,the material obstacles were the most common obstacles preventing theacquisition of automated systems in school libraries in Qena Governorate.The study recommended following the correct and modern methods whenplanning to acquire an automated system in school libraries In proportion theirneeds, requirements and the desired services, and invite the central institutionsto support school libraries in Qena Governorate to provide the necessaryfinancial capabilities for them so that they can provide the necessary equipmentand requirements to acquire and use automatic systems